Enhanced expression of 14-3-3 proteins in reactive astrocytes in Creutzfeldt-Jakob disease brains - Kawamoto, Yasuhiro; Akiguchi, Ichiro; Jarius, Christa; Budka, Herbert (Acta Neuropathologica, 2004)
14-3-3 proteins have been reported to be detected specifically in the cerebrospinal fluid (CSF) from patients with Creutzfeldt-Jakob disease (CJD). To elucidate the role of 14-3-3 proteins in patients with CJD, we performed immunohistochemical studies on 14-3-3 proteins in autopsied brains from five patients with sporadic CJD (sCJD), three patients with Alzheimer's disease (AD), and seven normal control subjects. Formalin-fixed, paraffin-embedded sections from all cases were immunostained with several types of specific anti-14-3-3 antibodies. In the normal control brains, 14-3-3 immunoreactivity was localized mainly in the neuronal somata and processes; in contrast, glial cells showed no or faint immunoreactivity. In the brains from the patients with AD, 14-3-3 immunoreactivity was observed in the surviving neurons as well as some neurofibrillary tangles. In the brains from the patients with sCJD, 14-3-3 immunoreactivity was well preserved in the remaining neurons. Furthermore, the glial cells, especially the reactive astrocytes, were intensely immunostained in the brains affected by sCJD. Our findings suggest that 14-3-3 proteins may be up-regulated in the glial cells, particularly in reactive astrocytes, and that the enhanced expression of 14-3-3 proteins in these glial elements may be associated with the pathogenesis of sCJD.